2018
DOI: 10.1007/s00586-018-5677-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi- versus single-level anterior cervical discectomy and fusion: comparing sagittal alignment, early adjacent segment degeneration, and clinical outcomes

Abstract: Two years following an ACDF, patients who underwent multi-level fusions appear to restore significantly greater amounts of lordosis compared to single-level procedures, while single-level ACDFs show significantly greater amounts of lordosis improvement over time. Multi-level procedures may not be at a significantly greater risk of developing early radiographic evidence of ASD compared to single-level procedure. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 30 publications
6
37
1
1
Order By: Relevance
“…Fusion status was also frequently assessed using dynamic lateral radiographs. Using this imaging technique, authors measured ISM (22 of 39, 56.4%) [ 10 , 13 , 14 , 16 , 19 - 22 , 25 , 28 , 29 , 31 , 33 - 39 , 41 - 43 ] or used the Cobb angle method (12 of 39, 30.8%) [ 11 , 15 , 17 , 27 , 32 , 34 , 37 , 42 - 46 ] to assess cervical fusion. No consensus was reached regarding the amount of motion for evaluation of cervical fusion on dynamic lateral radiographs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusion status was also frequently assessed using dynamic lateral radiographs. Using this imaging technique, authors measured ISM (22 of 39, 56.4%) [ 10 , 13 , 14 , 16 , 19 - 22 , 25 , 28 , 29 , 31 , 33 - 39 , 41 - 43 ] or used the Cobb angle method (12 of 39, 30.8%) [ 11 , 15 , 17 , 27 , 32 , 34 , 37 , 42 - 46 ] to assess cervical fusion. No consensus was reached regarding the amount of motion for evaluation of cervical fusion on dynamic lateral radiographs.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamic flexion-extension films can also assess for the change in Cobb angle between the adjacent fused vertebrae to determine postoperative fusion status. Recent literature frequently employed the change in Cobb angle as a criteria to confirm fusion (30.8%) [ 11 , 15 , 17 , 27 , 32 , 34 , 37 , 42 - 46 ], but the radiographic parameters ranged from 1.5 to 5 degrees. Cannada et al [ 4 ] showed that changes in Cobb angle of 2 degrees lead to a sensitivity of 82% and specificity of 39%.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the presence of ASD based on the modified Hilibrand criteria on radiography and computed tomography (CT) [1]. Radiographic ASD was determined by the presence of disc space narrowing >25%, new or enlarged osteophytes, anterior/posterior disc herniation, endplate sclerosis, and/or calcification of the anterior/posterior longitudinal ligaments as reported in previously published studies [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…During a longterm follow-up, our series provided comparable incidence of ASD between SSC and ACP although with a rate of more than 60%. While it was reported multi-level procedures may not be at a greater risk of developing ASD compared to single-level procedure [14]. Besides, the fact that no case with adjacent segment pathology for secondary surgery in either group and no significant change of UAL and LAL at FFU indicated the two approaches put little and comparable impact on the progression of ASD.…”
Section: Discussionmentioning
confidence: 90%
“…ACDF allows direct decompression of neural structures, reconstruction of cervical lordosis and stabilization of the operated segments [13]. Since the SSC system as a new-designed implant has been used for CSM, multiple studies mainly concentrated on the comparison between SSC and ACP in terms of surgery-related complications and clinical outcomes by a short-to middle-term cohort, having illustrated favorable outcomes [14][15]. Yun et al [16] conduct a 2-year follow-up on 2-level contiguous ACDF and showed compatible clinical outcomes and capacity of lordosis-maintenance between SSC and ACP.…”
Section: Discussionmentioning
confidence: 99%